Equivalence Strategy On Subtitling Of Green Lantern Movie - Atriyanto, Yogi, Dra. Dwi Haryanti, M. Hum, Dr. Anam Sutopo, S. Pd., M. Hum (2013)
This research studies about the strategy of equivalence on subtitling of Green Lantern movie. The research paper aims at describing the strategy used by subtitler to get equivalence in Green Lantern movie. The type of the study is qualitative study which is comparing the source language (SL) and target language (TL) of Green Lantern movie's subtitling. The method of data collection is documentation and technique of data analysis is comparison. The data are taken from the subtitling of Green Lantern movie. The results of the research show that; firstly, there are six equivalence strategies found in Green Lantern movie. They are transfer, paraphrase, condensation, imitation, deletion, and addition. From 1031 data, there are a) 463 data or 44. 91% data belong to transfer, b) 27 data or 2. 62% belong to paraphrase, c) 76 data or 7. 37% belong to condensation, d) 58 data or 5. 63% belong to imitation, e) 221 data or 21. 44% belong to deletion, and f) 186 data or 18. 04% belong to addition. In this research, transfer is dominant strategy used in subtitling. Secondly, Related to the equivalence translation, the researcher finds 971 data or 94. 18% belong to equivalent subtitling, while there are 60 data or 5. 82% belong to non equivalent subtitling. It means that the subtitling of Green Lantern movie has equivalent between source language (SL) and target language (TL).